Histopathological changes induce by piroxicam administration in kidneys of adult male albino mice Mus musculus - Intidhar M. Mnati; Bushra O. Maaroof (Journal of Madenat Alelem University College, 2017)
Piroxicam is one of non-steroidal anti-inflammatory drugs (NSAIDs) which is widely used in treating rheumatic disorders. The current study aimed to detect the deleterious effect of piroxicam pertaining to the chronic administration in male albino mice Mus musculus.A total number of (64) adult male albino mice were utilized in this study, they were randomly distributed into four main groups, the first three groups were orally treated with concentrations (50,100,150) mg/kg of piroxicam respectively, the forth group considered as control group were orally treated with distilled water for eight weeks, kidney samples were collected every two weeks for the histological study. This study recorded the presence of histopathological changes in the kidney of the treated mice with the concentration (50) mg/kg represented by hemorrhage, vascular congestion, calcium casts formation inside the lumens of renal tubules, while the groups treated with (100)mg/kg of the drug showed a fibrin deposition inside renal tubular lumens, infiltration of inflammatory cells, cytoplasmic vacuolation in the epithelial cells of the renal tubules and sloughing epithelium of renal tubules. The histological examination of mice kidneys treated with (150) mg/kg showed the appearance of hyalinization, shrinkage and complete loss of glomeruli, pyknosis of nuclei as well as the presence of oedema, in addition there were a remarkable decrease in the glycogen and protein contents of cells. The statistical results of the present study revealed a significant differences (P<0.05) in the mean diameters of renal glomeruli for all concentrations of the experiment for the period of eight weeks also there were significant decrease in the mean diameters of proximal convoluted tubules in the period of four weeks of the treated animals with concentrations (100 and 150) mg/kg as compared with control group. While the diameter of distal convoluted tubules showed a significant decrease with the concentrations (100 and 150)mg/kg for the periods six and eight weeks as compared with control group. It is clear from this study that piroxicam has drastic toxic effects on kidney tissue as represented by the observed histopathological changes.